ALGORITHMIC ASPECTS OF PREIMAGE SEARCH FOR HASH FUNCTIONS ON THE EXAMPLE OF MD5 - Кудін, Антон Михайлович; Коваленко, Богдан Анатолійович (Ukrainian Information Security Research Journal, 2015)
In this paper some issues of Aoki method for Merkle-Damgard hash functions preimage was considered. Insteadof the original method, which requires several differentialpaths for theoretical attack, we are targeted on generationof large set of high-probability differential paths. Methodsof set of high-probability differential paths generating wassuggested, complexity evaluation for reduced MD5preimage searching was obtained. These resultsdemonstrate weakness of reduced MD5 algorithm, alsothey provide additional constrictions for new hash functionconstructions.